Potential of Graphic Organizers in Developing Communicative Competence in Learning Russian as a Foreign Language - Sharofat T. Chorieva (Вестник Московского Университета. Серия 20: Педагогическое образование, 2025)
Background. Graphic organizers (in particular, the hierarchical diagram “How?” and the “Pyramid” scheme) play a significant role in the study of Russian as a foreign language by high school students. They contribute not only to the formation of foreign-language communicative competence, but also develop a creative approach, the ability to work in a team, logical-critical, systemic, creative thinking, and independent work skills. In scientific literature, the potential of graphic organizers has not been sufficiently considered, since they are most often described without completed samples. Teaching Russian with the help of graphic organizers in schools with Uzbek and other languages of instruction will simplify, systematize and interestingly design the educational material.